Pemanfaatan Tumbuhan dalam Pengobatan Tradisional Masyarakat Suku Dayak Kanayatn di Desa Ambawang Kecamatan Kubu Kabupaten Kubu Raya - Riza Linda, Fadilah, Irwan Lovadi (Universitas Tanjungpura, 2015)
The aim of this research was to find out the system of traditional medicine of the Kanayatn Dayak community in Ambawang Village, plant species and parts that were used as well as the form, method and use value ​of the plants. This research was carried out in May 2014 to January 2015 in Ambawang Village, Kubu Sub-District, Kubu Raya Regency The respondents were selected using the snowball method, whereas the information on the traditional medicine was obtained from interviews with the respondents. The date were analyzed using both qualitative and quantitative analysis. The qualitative analysis was conducted to find out the types of plants, parts that wre used, procedure, method and forms of use. The quantitative analysis used Frequency of Citation (FIC), Plant Part Value (PPV) and Interspecific Use Value (IUV). The research findings showed that the system of the traditional medicine of the Kanayatn Dayak community categorized ilness into two types, i.e. based on the causes, illnesses caused by non-supernatural elements and by supernatural elements. The non-supernatural illnesses were treated using medicinal herbs, massage and other physical treatments, while illnesses caused by supernatural elements were treated with a healing ritual. There were 45 types of plants used in traditional medicine namely 28 types for healing non-supernatural illnesses, and 17 species for healing supernatural illnesses. The parts of the plant used were the stem, fruit, leaf, flower, root, rhizome, tuber and sap. Both fresh and dried plants were used. The methods of use were by way of grinding, boiling, rubbing, attaching, burning and pounding and making it a component of the healing ritual. The highest FIC was 100%, the PPV of the plants used in the traditional medicine of the Kanayatn Dayak community was from 0.133 to 1, and the IUV was from 0.176 to 1.